Showcasing information outcome of the Farmer FIRST Programme - Horam, Yaoreiphy; Kumar, Aruna T; Singh, Shantanu Kumar; Roy, Mitali Gosh; Kumar, Shiv; Chahal, V P; Singh, S K (Indian Farming, 2019)
Farmer FIRST Programme—Farm, Innovations, Research, Science and Technology (FIRST), brings the scientists and lab in the fields of farmers, putting farmers in the centre of the research programme, was initiated by the ICAR in 2016 to double the farmers’ income by 2022. It will be achieved with focus on innovations, technology, feedback, multiple stakeholder participation, multiple realities, multi method approaches, vulnerability and livelihood interventions.